Impact of Brand Awareness on Small and Medium Enterprises in Kenya - Muchori, Margaret Muthoni; Reid, Patrick (Journal of Business and Strategic Management, 2025)
Purpose: This study explores the impact of brand awareness on the performance of small and medium enterprises (SMEs) in Kenya. Methodology: Guided by a positivist philosophy, the research employed a mixed methods approach to gather and analyze both quantitative and qualitative data. A total of 385 questionnaires were administered to SME stakeholders, with primary data collected for analysis. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative responses were examined thematically. Findings: The findings indicate that brand awareness particularly through social media platforms is a crucial determinant of SME success. Active social media engagement enhances brand recognition, fosters trust, increases visibility, and contributes to improved customer acquisition and retention. Comments and feedback from social media users serve as a vital input in shaping product design and marketing strategies, underscoring the role of customer perceptions in building brand identity. Unique Contribution to Theory, Practice and Policy: The study recommends that SMEs adopt structured social media management strategies focused on increasing brand visibility. This includes providing timely, personalized responses to customer inquiries and leveraging visually appealing content to enhance brand recall and engagement.